Peningkatan Kesadaran Anemia Pada Remaja di SMP Negeri 3 Mande Desa Jamali, Cianjur: Increased Awareness of Anemia Among Adolescents in SMP Negeri 3 Mande Jamali village Cianjur - Bere, Contriana Yusinta; Sianturi, Sondang Ratnauli; Ides, Stefanus Andang; Priyono, Adinda Eka; Umboh, Michael Hendich; Kususma, Clara Rida; Harefa, Fetrianika; Oktavian, Agnes Vanessa Natalia (Sam Ratulangi University, 2025)
One of the achievements of the smart village program is to increase community awareness and participation in village development and improve the quality of life of village communities. Therefore, the Sint Carolus School of Health Sciences (STIK) collaborates with four other universities to achieve a common goal, namely to educate and increase understanding and awareness in adolescents of quality of life and productivity from an early age. The prevalence of anemia in Indonesia is most common in adolescent girls aged 15-24 years at 79%. For this reason, this activity was carried out with the aim of increasing the knowledge of adolescents, especially young women, about the importance of fulfilling nutrition in preventing anemia which was held on December 9, 2024, at the Hall of SMP Negeri 3 Mande, Jamali Village, Cianjur Regency, West Java. The method of implementing the activity includes a pre-test to see the extent of adolescent knowledge about anemia, then given counseling education about anemia in adolescents, providing anemia learning videos to adolescents, interactive discussions and feedback, then ending with a post-test to see the extent of adolescent knowledge or understanding after being given anemia material. The results of these activities showed a very significant increase between before and after counseling. The teenagers were very enthusiastic and participated in increasing their knowledge about anemia in adolescents, so it was very evident in the results of discussions and very constructive feedback. This counseling activity is very beneficial for adolescents so that it can increase self-awareness in fulfilling the correct nutrition from an early age, and can be a form of prevention against the risk of unplanned pregnancy and complications due to early marriage that often occur in Jamali Village. ABSTRAK Salah satu capaian pada program smart village adalah meningkatkan kesadaran dan partisipasi masyarakat dalam pengembangan desa serta meningkatkan kualitas hidup masyarakat desa. Oleh karena itu, Sekolah Ilmu Tinggi Kesehatan (STIK) Sint Carolus berkolanorasi dengan empat perguruan tinggi lainnya untuk mencapai tujuan bersama yaitu mencerdasakan serta meningkatkan pemahan dan kesadaran pada remaja akan kualitas hidup dan produktivitas sejak dini. Prevalensi anemia di Indonesia paling sering terjadi pada remaja wanita dengan usia 15-24 tahun sebesar 79%. Untuk itu, kegiatan ini dilakukan dengan tujuan meningkatkan pengetahuan remaja khususnya remaja putri akan pentingnya pemenuhan nutrisi dalam mencegah anemia yang dilaksanakan pada tanggal 09 Desember 2024, di Aula SMP Negeri 3 Mande Desa Jamali, Kabupaten Cianjur, Jawa Barat. Metode pelaksanaan kegiatan meliputi pre-test untuk melihat sejauh mana tingkat pengetahuan remaja tentang anemia, kemudian diberikan edukasi penyuluhan tentang anemia pada remaja, pemberian video pembelajaran anemia pada remaja, diskusi interaktif dan umpan balik, lalu diakhiri dengan post-test untuk melihat sejauh mana tingkat pengetahuan atau pemahaman remaja setelah diberikan materi anemia. Hasil dari kegiatan tersebut menunjukan adanya peningkatan yang sangat signifikan antara sebelum dan sesudah diberikan penyuluhan. Para remaja sangat antusias dan berpartisipasi dalam meningkatkan pengetahuannya tentang anemia pada remaja, sehingga sangat terlihat pada hasil diskusi dan umpan balik yang sangat konstruktif. Kegiatan penyuluhan ini sangat bermanfaat bagi para remaja sehingga dapat meningkatkan kesadaran akan diri sendiri dalam pemenuhan nutrisi yang benar sejak dini, serta dapat menjadi salah satu bentuk pencegahan terhadap resiko kehamilan tidak terencana dan komplikasi akibat pernikahan dini yang sering terjadi di Desa Jamali.